ANALISIS PERAMALAN HARGA EMAS DI INDONESIA PADA MASA PANDEMI COVID-19 UNTUK INVESTASI - Nasrudin Nasrudin; Dyah Makutaning Dewi; Muhammad Zaky Nafi' (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
Pandemic Coronavirus Disease-2019 (Covid-19) is an unusual occurrence. The Covid-19 makes people hesitant to invest. This is because the world economy is not in good condition. Gold investment is one of the safest investments during the Covid-19 pandemic. The precious metal is widely chosen because the majority of the public is familiar with gold and easy to reach. In addition, because the price of gold tends to be stable and rarely inhabits the price drop, it is actually currently experiencing an increase in the price in a short time. One way to know the picture of gold price in Indonesia so that people are interested in investing in precious metals is to do forecasting using ARIMA Box-Jenkins method. The purpose of this research is to obtain gold price predictions in Indonesia over the next 30 days. The results of the analysis showed that ARIMA model (1,1,1) so that it can be concluded that the gold price prediction of the next 30 days continues to increase with the percentage of training data errors by 1,005 percent and the validation of the forecast from testing data by 3,93 percent.